1H NMR-based metabolomics revealed the protective effects of Guilingji on the testicular dysfunction of aging rats. (28th June 2019) - Zhao, Si-jun; Tian, Jun-sheng; Tai, Gang; Gao, Xiao-xia; Liu, Hua-lan; Du, Guan-hua; Liu, Xiao-jie; Qin, Xue-mei
Abstract: Ethnopharmacological relevance: Guilingji (GLJ), a famous and classical traditional Chinese medicine (TCM) prescription, has been used to extend the lifespan and improve the life qualities of the elderly for hundreds of years in China. Aim of the study : We aimed to explore the protective effects of GLJ on the testicular dysfunction of aging rats, as well as the regulating effects of GLJ on the metabolic disturbance and metabolite changes in natural aging rats. Materials and methods: Forty 23-month-old rats were divided randomly into four groups, including the old control group and three groups of GLJ treatment at 37.5, 75, and 150 mg/kg doses, respectively. Additionally, 10 four-month rats were included as the youth control group. Testicular dysfunction was first evaluated by measuring the changes in the wet weights of the testicles, concentration of serum testosterone (T), and morphologic changes of the testis. Subsequently, an 1 H NMR-based metabolomics approach coupled with multivariate analysis, including partial least squares discriminant analysis (PLS-DA) and orthogonal partial least squares-discriminant analysis (OPLS-DA) was applied to monitor the metabolite changes. Results: Compared with the old control group, the wet weights of the testicles and T concentration were significantly increased, while the morphologic abnormality of testicular tissues was improved by a 4-week treatment course with GLJ. Furthermore, compared with the old control group, the urinary levels of alanine, pantothenate, phenylalanine, β-hydroxybutyrate and pyruvate were significantly decreased after a 4-week treatment course with GLJ. Additionally, we found that amino acid metabolism and pyruvate metabolism were significantly involved in the regulatory effect of GLJ. Conclusions: The current findings provided, for the first time, sound evidence of the protective effects of GLJ on testicular dysfunction from both biochemical and metabolomics perspectives. The mechanisms of GLJ could be related to regulating amino acid metabolism and pyruvate metabolism. The current study lays an important foundation for further research and for the broad clinical application of GLJ. Graphical abstract: Image 1